The ejection fraction and the cardiac index in the perioperative period of coronary artery bypass grafting: what is worth relying on? - Konstantin V. Paromov; Ayyaz Hussain; Lyudmila A. Neledova; Mikhail Y. Kirov (Alʹmanah Kliničeskoj Mediciny)
Rationale: Ejection fraction (EF) has been recognized as a key echocardiographic parameter describing the systolic function of the heart. Nevertheless, its accuracy for the assessment of the hemodynamic status in the perioperative period of cardiac surgery remains a debate.